Prevalence and Intensity of Ectoparasites on Clarias gariepinus From Aquaculture Pond in Aceh Besar District, Indonesia - Fitria Nelda Fautama; Ilham Zulfahmi; Muliari Muliari; Adian Aristia Anas (UIN Sunan Gunung Djati Bandung, 2019)
Information related to the prevalence and intensity of para-sites in an aquatic environment is crucial as preventive and responsive efforts to manage aquatic resources, especially for fish farming pur-poses. Up to now, information related to the prevalence and intensity of ectoparasites on catfish from aquaculture ponds in Aceh Besar Dis-trict is rare. This study aims to investigate the prevalence, intensity, and dominance of ectoparasites on catfish from aquaculture ponds in Aceh Besar district. The total of 200 catfish from four research stations at Sibreh, Kareung, Lambaro, and Limpok was observed in this study. The ectoparasites observation was focused on the skin, fins, and gill of the catfish. The observation parameter consists of prevalence, in-tensity, domination, length-weight relationship, and condition factor. Identification result showed that there were four types of ectoparasites infect the catfish in the aquaculture ponds in Aceh Besar District i.e Trichodina sp., Gyrodactylus sp., Dactylogyrus sp. and Ichthyopthyri-us multifiliis. Station 3 (Lambaro) had the highest prevalence and in-tensity, which were 64% and 5.87 ectoparasites/fish, respectively. In-fected catfish tended to have a lower weight growth than healthy catfish.